Students’ Preferred Instructional Practices - Arzagon, Rosmalin G.; Zaragoza, Melody A.; Mecida, Sherry V. (ASEAN Journal of Educational Research and Technology, 2023)
The main objective of this descriptive research was to find out the students’ preferred instructional practices during the global pandemic. The respondents were 308 students coming from 11-course offerings enrolled during the first semester of the academic year 2021-2022. The study was conducted at Notre Dame of Tacurong College, Tacurong, Sultan Kudarat Province, the Philippines. Findings showed that the mean ratings of the eight items ranged from 2.64 to 6.24. Since ranking was used to determine the most and least preferred instructional practices, the item with the least mean rating is ranked 1, and the item with the highest mean rating is ranked 8. Hence, the three most preferred instructional practices are: Item 1, Assignments that ask students to express what they have learned and what they still need to learn, obtained the weighted mean of 2.64 (SD = 2.24) and interpreted as Strongly Preferred; Second is Item 3, Live sessions “zoom meetings” in which students can ask questions and participate in discussions, got the weighted mean of 3.31 (SD = 1.74) and interpreted as Preferred; and the third is Item 2, Frequent quizzes or other assessments, obtained a weighted mean of 3.44 (SD = 2.10) and interpreted as Preferred.